Newborn screening for aromatic l-amino acid decarboxylase deficiency: strategies, results, and implication for prevalence calculations - Reischl-Hajiabadi, Anna Theresa; Okun, Jürgen G.; Kohlmüller, Dirk; Manukjan, Georgi; Hegert, Sebastian; Durner, Jürgen; Schuhmann, Elfriede; Hörster, Friederike; Mütze, Ulrike; Feyh, Patrik; Hoffmann, Georg F.; Röschinger, Wulf; et al. (Molecular genetics and metabolism, 2024)
Background - Aromatic l-amino acid decarboxylase deficiency (AADCD) is a rare, autosomal-recessive neurometabolic disorder caused by variants in dopa decarboxylase (DDC) gene, resulting in a severe combined deficiency of serotonin, dopamine, norepinephrine, and epinephrine. Birth prevalence of AADCD varies by population. In pilot studies, 3-O-methyldopa (3-OMD) was shown to be a reliable biomarker for AADCD in high-throughput newborn screening (NBS) allowing an early diagnosis and access to gene therapy. To evaluate the usefulness of this method for routine NBS, 3-OMD screening results from the largest three German NBS centers were analyzed. - Methods - A prospective, multicenter (n = 3) NBS pilot study evaluated screening for AADCD by quantifying 3-OMD in dried blood spots (DBS) using tandem mass spectrometry (MS/MS). - Results - In total, 766,660 neonates were screened from January 2021 until June 2023 with 766,647 with unremarkable AADCD NBS (766,443 by 1st-tier analysis and 204 by 2nd-tier analysis) and 13 with positive NBS result recalled for confirmatory diagnostics (recall-rate about 1:59,000). Molecular genetic analysis confirmed AADCD (c.79C > T p.[Arg27Cys] in Exon 2 und c.215 A > C p.[His72Pro] in Exon 3) in one infant. Another individual was highly suspected with AADCD but died before confirmation (overall positive predictive value 0.15). False-positive results were caused by maternal L-Dopa use (n = 2) and prematurity (30th and 36th week of gestation, n = 2). However, in 63% (n = 7) the underlying etiology for false positive results remained unexplained. Estimated birth prevalence (95% confidence interval) was 1:766,660 (95% CI 1:775,194; 1:769,231) to 1:383,330 (95% CI 1:384,615; 1:383,142). The identified child remained asymptomatic until last follow up at the age of 9 months. - Conclusions - The proposed screening strategy with 3-OMD detection in DBS is feasible and effective to identify individuals with AADCD. The estimated birth prevalence supports earlier estimations and confirms AADCD as a very rare disorder. Pre-symptomatic identification by NBS allows a disease severity adapted drug support to diminish clinical complications until individuals are old enough for the application of the gene therapy.